2008
DOI: 10.1002/ajmg.b.30803
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cognitive impairment in female premutation carriers of fragile X premutation: Analysis by means of robust segmented linear regression models

Abstract: This report describes a study focused on the relationship between CGG repeat length, FMRP, mRNA levels and cognitive functioning in premutation carriers (PM) carriers of Fragile X Syndrome (FXS). We studied 60 females-43 with PM and 17 with normal (N) alleles-from 25 FXS Spanish families. The Wechsler scales were administered to all subjects and new blood samples and hair roots were taken to study mRNA and FMRP levels. Using lowess curves together with segmented models we showed that within the premutation ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…While in PM women one study showed that CGG repeat size, when controlled for AR, was significantly associated with ataxia score, 7 the prognostic utility of AR in blood, when examined alone, has not been demonstrated previously. 7,22 In contrast, decrease in FMRP levels in hair root samples was significantly correlated with cognitive status of PM women. 22 Subsequently, it has been suggested that methylation of the CpG sites used to determine AR is not well conserved between blood and other tissues, and thus provides limited representation of FMRP activity in the brain.…”
Section: Relationships Between Molecular Parametersmentioning
confidence: 87%
See 2 more Smart Citations
“…While in PM women one study showed that CGG repeat size, when controlled for AR, was significantly associated with ataxia score, 7 the prognostic utility of AR in blood, when examined alone, has not been demonstrated previously. 7,22 In contrast, decrease in FMRP levels in hair root samples was significantly correlated with cognitive status of PM women. 22 Subsequently, it has been suggested that methylation of the CpG sites used to determine AR is not well conserved between blood and other tissues, and thus provides limited representation of FMRP activity in the brain.…”
Section: Relationships Between Molecular Parametersmentioning
confidence: 87%
“…7,22 In contrast, decrease in FMRP levels in hair root samples was significantly correlated with cognitive status of PM women. 22 Subsequently, it has been suggested that methylation of the CpG sites used to determine AR is not well conserved between blood and other tissues, and thus provides limited representation of FMRP activity in the brain. 22 Our previous studies suggest that methylation of FMR1 intron 1 CpG sites is well-conserved between different tissue types including adult and newborn blood, lymphoblasts, and amniocytes, and is stable over time in PM females.…”
Section: Relationships Between Molecular Parametersmentioning
confidence: 87%
See 1 more Smart Citation
“…A combination of high CGG repeat size and low FMRP expression may further enhance vulnerability. In female carriers with over 100 CGG repeats and FMRP expression in hair roots below 60%, a 10% decrement of FMRP expression corresponded to a significant decrease in IQ scores by about six points [28]. …”
Section: Cognitive Deficits In Premutation Carriersmentioning
confidence: 99%
“…Segmented regression has previously been applied to link CGG repeats to mRNA levels in trinucleotide repeat disorders patients (Garcia-Alegria et al, 2007;Minguez et al, 2009) and gene compactness driven nonmonotonic expression levels in eukaryote cells (Carmel and Koonin, 2009).…”
mentioning
confidence: 99%